Focal reduction of villous blood flow in early indomethacin enteropathy: a dynamic vascular study in the rat. Issue 3 (1st March 1998) - Kelly, D A; Piasecki, C; Anthony, A; Dhillon, A P; Pounder, R E; Wakefield, A J
Abstract : Background —Oral indomethacin causes villous shortening, microvascular damage, and distortion, which might induce mucosal ischaemia and necrosis. Aims —In order to determine the early events in indomethacin induced jejunal injury we examined the temporal relations between morphological damage and changes in villous blood flow following indomethacin. Methods —In anaesthetised rats, mid jejunal villi were exteriorised in a chamber and observed by fluorescence microscopy. Blood flow in surface capillaries was calculated from velocities and diameters. Indomethacin was applied by both luminal and intravenous routes for 90 minutes, after which the animal was perfusion fixed and the villi were processed for histological examination. Control animals received intravenous or luminal bicarbonate (1.25%). Results —Blood flow slowed in individual villi at 20 minutes, and progressed to complete stasis (in another group) by 45 minutes. Histological examination at 20 minutes revealed microvascular distortion, but no villous shortening: crypt depth:villous height ratios were 0.356 (0.02) in test and 0.386 (0.01) in surrounding villi (p>0.5). At stasis, the villi under study showed epithelial clumping and were shortened: crypt depth:villous height ratios were 0.92 (0.2) in test and 0.42 (0.06) in surrounding villi (p<0.02). Vehicle alone had no effect on either blood flow or histology. Conclusions —Focal slowing of villous blood flow and microvascular distortion precede villus shortening and epithelial disruption, and indicate that damage to surface microvasculature is an early event in indomethacin induced mucosal injury in this model.